The Effectiveness of Implementing a New Barcode System in Reducing Errors in Blood Component Dispensing at the Blood Bank of Loei Hospital - ถิ่นสพุง คงเดช (Journal of Health Science of Thailand, 2026)
In the process of blood component transfusion in blood bank of various hospitals, barcode systems have been employed to prevent errors and ensure the safe delivery of blood to patients. Data from the blood bank at Loei Hospital indicate that between 2022 and February 2023, despite using the existing barcode system for blood component transfusion, there was still an error rate of 0.013. The objective of this study was to investigate the error rate in blood component transfusion using a new barcode system. The study method involved enhancing the barcode system by adding an additional barcode verification of blood requisition slips and blood components, which was integrated with the hospital’s Hospital Information System (HIS) and Laboratory Information System (LIS). Data were collected from March 2023 to 2024. The results showed that the error rate in blood and blood component transfusion was 0%. In conclusion, the errors rate in blood component transfusion using the new barcode system at the blood bank of Loei Hospital was 0%. It is recommended that the new barcode system be implemented in other blood banks in hospitals to further reduce errors in blood component transfusion.